Navigating Security in the Pacific - Greener B; Noa A (Macmillan Brown Centre for Pacific Studies, University of Canterbury, 2020)
This article examines how New Zealand has framed recent security dynamics in the region and asks how this framing aligns with the priorities of Pacific partners. There are some indications of increasing alignment with ‘like-minded’ partners such as the US and Australia, prompted in part by increased concerns about Chinese engagement in the region. However, New Zealand has also been circumspect in seeking out opportunities to continue to engage with China and, perhaps most importantly for its Pacific partners, has increasingly responded to regional concerns about understanding climate change as an existential security threat. Recent uptake of Pacific imagery and narrative in the Ministry of Defence's Advancing Pacific Partnerships policy document is particularly evocative in suggesting a more genuine recentring of Pacific priorities, although enduring engagement is needed to support rhetorical commitments (New Zealand Ministry of Foreign Affairs and Trade, 2018). Here relationships with diasporic populations, youth and women, in particular, should be more strongly pursued as New Zealand navigates its way in and through the Pacific and its politics into the future.
Keywords: women; diaspora; youth; Pacific politics; recentring; framing; Regional geopolitics